FACTORS ASSOCIATED WITH FOOD SAFETY KNOWLEDGE AND PRACTICE AMONG STREET FOOD VENDORS IN TAUNGGYI TOWNSHIP, MYANMAR: A CROSS-SECTIONAL STUDY - Soe Htway, Tin Aung; Kallawicha, Kraiwuth (Malaysian Journal of Public Health Medicine, 2020)
Food safety is a growing public health concern worldwide. Street foods are an integral part of many cultures and offer at affordable prices. However, it is associated with food safety issues, especially in developing countries. Therefore, it is essential that street food vendors understand and implement food safety practices to prevent outbreaks of food-borne illnesses. This cross-sectional study investigated the food safety knowledge and practices as well as their associated factors among street food vendors in Taunggyi Township, Myanmar. Validated structured questionnaires were used to interview 158 street food vendors, and a set of observational checklists was used to inspect the sanitary conditions of vending sites and vendors’ food hygiene practices. The association between food safety knowledge and practices was assessed using a chi-squared test. Our results revealed that most vendors had a high level of food safety knowledge and that 58.9% scored equal to or lower than the median value in food safety practices, whereas 41.1% scored higher than the median value (median=15). Sex and education level were significantly associated with participants’ food safety knowledge (p < 0.001). Similarly, education, race and monthly income were significantly associated with their food safety practices (p < 0.001), whereas food safety training attendance had no association. Additionally, participants with better knowledge scores were more likely to have better practice scores. Food safety training given to vendors should be more detailed and comply with standard guidelines, especially with regard to street food safety practices.